Improving Mathematics Problem Solving Ability through Team Assisted Individualization Learning Model - Arrahim Arrahim; Rini Endah Sugiharti; Desinta Damayanti (Program Studi Tadris Matematika IAIN Salatiga, 2020)
The purpose of this study was to improve students' problem-solving abilities using the Team Assisted Individualization (TAI) model in students grade IV of Bekasi Jaya II State Elementary School. This study was carried out because of the students' low problem-solving ability in Mathematics.This study employed the Classroom Action Research approach, which was conducted in two cycles. Each cycle has four stages, namely, planning, implementation, assessment, and reflection stage. About 27 students from grade IV has participated in this study. Data collection was carried out through written tests and observation sheets. Data were analyzed with descriptive analysis. The criterion for success in this study is if 80% of students achieve a minimum score of 75.Based on the results, the students' problem-solving ability in cycle I with classical completeness was 59%, and got an average score of 72. In cycle II with 89% classical completeness, and the mean score of students' problem-solving abilities increased to 88. Thus, it can be concluded that the Team Assisted Individualization model can improve the conceptual understanding of grade IV students of Bekasi Jaya II State Elementary School.